The Effect of Fibre Compositions and Fabric Constructions on Elastic Properties of Compression Fabrics (Journal of Fiber Bioengineering and Informatics, 2024)
This study aimed to investigate the impact of varying fibre compositions and fabric constructions on theelastic behaviour of compression fabrics. Knitted fabrics used as compression garments are subjectedto deformation due to various loads used to extend the fabrics during wear. The loads to extend thefabrics are influenced by fabric constructions, strain levels and fabric directions. In this study, the strainof fabrics was measured using a commercial tensile testing machine (LR30K Lloyd) according to ASTMD496. Each sample was cycled five times between zero and the specified strain to replicate the repeateduse of compression garments. In addition, the fabric was also heat-set and laundered to evaluate theimpact of these treatments on the elastic behaviour of the fabric. The results indicated that differentfabric constructions exhibited different elastic properties $(P
Keywords: compression fabric; fabric constructions; elastic behavior; tension decay; heat setting.